From the street corner to call centre: changes in the characteristics of mental health-related calls for service received by police - Hendy, Ross (Policing and society, 2022)
Between 2009 and 2016, New Zealand Police experienced a disproportionate increase in lower-priority mental health-related calls. This exploratory study uses content analysis to identify characteristics of these calls, including reasons for calling police, advice and actions undertaken by communications centres staff, and actions undertaken by frontline officers. Four important findings emerge. First, there has been a significant increase in the proportion of mental health-related calls that did not involve reporting of an offence or emergency (increased from 48% in 2010 to 57% in 2016). Second, there was a significant increase in calls that were initiated by the person who appeared to be experiencing mental illness and distress during the time of the call (increased from 53% to 62%). Third, the way communication centres staff and frontline officers responded to mental health-related calls also changed over time. There was an increased tendency of communications centre staff advising the callers to call back if the situation escalates or if they require further assistance (which increased from 14% to 24%). Fourth, among the events attended by a police unit, there was an increase in the proportion of events where a frontline officer contacted a mental health agency (which increased from 6% of attended events to 10%). Moreover, transportation to a police station decreased (21.7% to 11%) while there were increases in the transportation of a person’s home (2.7% to 6%). Transportation to a mental health facility averaged at 24.9% over the period.